Variabilidad en la respuesta al Clortoluron de los cultivares de Triricale "Badiel" y "Tajuña" - Sixto, H.=700 1 Muñoz, N; Chueca, M.C.; Garcia-Baudin, J.M.
(Es, En)
ilus., 22 ref.
Keywords: HERBICIDAS; TRITICOSECALE; FLUORESCENCIA; ESPAÑA; ESPAÑA; CLORTOLURON